Peran Vital Garbage Management Plan Dalam Mencegah Polusi Laut : Kajian Implementasi dan Dampaknya - Welem Ada (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
In order to prevent marine pollution on board a motor ship, this study examines how the Garbage Management Plan (GMP) has been implemented. This study analyzes the elements that influence the success of GMP, such as regulatory requirements, crew training and awareness, availability of infrastructure and resources, monitoring, and law enforcement. This is done through examining the implementation and impact of GMP. Methods of literature study, questionnaires, interviews, and qualitative analysis were used in this study. The findings of this study show how important GMP implementation is in minimizing marine pollution. The success of GMP is greatly influenced by adherence to clear and stringent regulatory standards. Successful implementation also depends on crew training and awareness. In addition, the effectiveness of GMP in motor ships depends on the availability of adequate infrastructure and resources. Preventing marine pollution has a positive impact with effective GMP monitoring and enforcement.